2020
DOI: 10.3390/publications8010006
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Environmental Monitoring as a Barrier to the Availability and Accessibility of Open Access Data on the Tidal Thames

Abstract: Open Access data plays an increasingly important role in discussions of environmental issues. Limited availability or poor quality data can impede citizen participation in environmental dialogue, leading to their voices being undermined. This study assesses the quality of Open Access environmental data and barriers to its accessibility in the Thames Estuary. Data quality is assessed by its ability to track long-term trends in temperature, salinity, turbidity, and dissolved oxygen. The inconsistencies found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…The study has, however, found knowledge and interpretation discrepancies between the validation practices and the decision-making practices; there is no clear consensus of how to apprehend data validity. Intermediary participants can serve to minimise the distance between variations of positions in Artportalen, resolving issues of unclear documentation reported in previous research (Lanoue, 2020). Contributing to scholarly information practices research on materiality (e.g.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study has, however, found knowledge and interpretation discrepancies between the validation practices and the decision-making practices; there is no clear consensus of how to apprehend data validity. Intermediary participants can serve to minimise the distance between variations of positions in Artportalen, resolving issues of unclear documentation reported in previous research (Lanoue, 2020). Contributing to scholarly information practices research on materiality (e.g.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Peer production of knowledge comprises a recurring area of investigation both in library and information science and in citizen science research. Library and information science research have been occupied with exploring scholarly information practices through material aspects (Pilerot et al, 2017), reading practices in scholarly work (Late et al, 2019) and co-production of knowledge (Lanoue, 2020). Citizen science research has been particularly engaged with understanding modes of participation and typologies of citizen scientists (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations